2016
DOI: 10.1590/s0080-623420160000100012
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip strength and physical activity in frail elderly

Abstract: Objective:To investigate the association between handgrip strength (HS) and physical activity in physical frailty elderly. Method: Cross-sectional quantitative study with a sample of 203 elderly calculated based on the population estimated proportion. Tests were applied to detect cognitive impairment and assessment of physical frailty. Descriptive statistics and multivariate analysis by binary logistic regression were used, and also Student's t-test and Fisher's exact test. Results: A total of 99 (64.3%) elder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
1
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 24 publications
3
17
1
15
Order By: Relevance
“…This may be due to insulin resistance in diabetes which leads to muscle strength decline [25]. Older people with hypertension, hypercholesterolemia, depression, and low physical activity are reported to have lower HGS [6,7,14]. Nevertheless, no statistically significant association was found between HGS and these conditions in this study.…”
Section: Discussioncontrasting
confidence: 61%
“…This may be due to insulin resistance in diabetes which leads to muscle strength decline [25]. Older people with hypertension, hypercholesterolemia, depression, and low physical activity are reported to have lower HGS [6,7,14]. Nevertheless, no statistically significant association was found between HGS and these conditions in this study.…”
Section: Discussioncontrasting
confidence: 61%
“…Grip strength is known to represent the overall muscle strength and functional capacity of an individual, and has been used as an important clinical tool to assess early symptoms of frailty in ageing individuals. [8][9][10][11][12][13] Additionally, normative reference values for specific populations, such as those in Singapore, South Korea, Canada and Europe, have been established, 15,[24][25][26][27] and cutoff grip strength values to screen elderly people at risk have also been implemented. [28][29] For example, the Asian Working Group for Sarcopenia 29 suggested that grip strength below 26 kg for males or 18 kg for females would signify a higher risk of sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 Hand grip strength measurement has been known to be a useful tool for assessing overall muscle weakness and identifying elderly people at risk of functional deterioration or frailty. [8][9][10][11][12][13] Taekema et al reported that lower grip strength was able to predict an accelerated decline in activities in daily living (ADL) functionality. 11 In a systematic review by Bohannon et al, the authors found that low grip strength was associated with a greater likelihood of functional limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers report that this difference is related to intrinsic factors, such as pathologies, as well as with life habits and socioeconomic aspects (24) . Practicing some physical activity, even with low intensity, is one of the main addressed factors, since its decrease is constantly related to the increase in the fragility and stillness of the senior citizen (25) . In this context, the use of the proposed walker with trunk support may help the performing low intensity physical activities, such as walks.…”
Section: Discussionmentioning
confidence: 99%